2006
DOI: 10.1111/j.1460-9568.2006.04770.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory changes in the hippocampus of somatostatin knockout mice: upregulation of somatostatin receptor 2 and its function in the control of bursting activity and synaptic transmission

Abstract: Somatostatin-14 (SRIF) co-localizes with gamma-aminobutyric acid (GABA) in the hippocampus and regulates neuronal excitability. A role of SRIF in the control of seizures has been proposed, although its exact contribution requires some clarification. In particular, SRIF knockout (KO) mice do not exhibit spontaneous seizures, indicating that compensatory changes may occur in KO. In the KO hippocampus, we examined whether specific SRIF receptors and/or the cognate peptide cortistatin-14 (CST) compensate for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 80 publications
8
51
2
Order By: Relevance
“…In turn, our finding of decreased LTP in CA1 upon somatostatin deficiency seems at odds with previous observations of an increase in basal synaptic transmission and shortterm plasticity, but unaltered LTP, after sst2 gene invalidation (Dutar et al 2002). It should be kept in mind, however, that multiple somatostatin receptors are expressed in the hippocampus, and that compensatory changes may occur after invalidation of the somatostatin gene (Cammalleri et al 2006) and possibly also the sst2 gene. The combination of genetic and pharmacological experiments, however, enabled us to control for such compensations, and to investigate the net effect of somatostatin on hippocampal plasticity, critical for our behavioral findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In turn, our finding of decreased LTP in CA1 upon somatostatin deficiency seems at odds with previous observations of an increase in basal synaptic transmission and shortterm plasticity, but unaltered LTP, after sst2 gene invalidation (Dutar et al 2002). It should be kept in mind, however, that multiple somatostatin receptors are expressed in the hippocampus, and that compensatory changes may occur after invalidation of the somatostatin gene (Cammalleri et al 2006) and possibly also the sst2 gene. The combination of genetic and pharmacological experiments, however, enabled us to control for such compensations, and to investigate the net effect of somatostatin on hippocampal plasticity, critical for our behavioral findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Among synthetic ligands, we used the peptidyl multiligand analog SOM230, which binds with high affinity to sst 1,2,3,5 [42][43][44], and the peptidyl multiligand analog KE108, which binds with high affinity to all five SRIF receptors [44,45]. The sst 1 -selective peptidyl agonist CH-275 [35,41,46,47], the sst 2 -preferring peptiydyl agonist SMS 201-995 (also known as sandostatin or octreotide) [38,41,46,48,49], and the sst 2 -selective nonpeptidyl agonist L-779,976 [46, 49 -51] were also used in the absence or presence of the sst 1 -selective nonpeptydil antagonist SRA-880 [46,52,53] and the sst 2 -selective peptydil antagonist CYN [36,38,48,49,54]. All compounds were applied at 1 M, which from previous studies, is a concentration giving maximal re- ceptor occupancy [2,41].…”
Section: Expression Of Srif Receptor Mrnas In Human Macrophagesmentioning
confidence: 99%
“…Using published protocols [35,36], the cells were fixed in 4% paraformaldehyde for 10 min at room temperature before washing with 0.1 M PB. The polyclonal antibodies directed against sst 1 and the sst 2A isoform of sst 2 [37,38] were diluted 1:100 in PB containing 0.1% Triton X-100 overnight at 4°C. Cells were then washed in PB and incubated in the presence of the appropriate secondary antibodies conjugated with Alexa Fluor 488 fluorescent dyes at a dilution of 1:200 in PB containing 0.1% Triton X-100 for 1 h at room temperature.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…One study reported an intracellular Ca 2+ -dependent modulation of AMPA currents postsynaptically, mediated by sst2 activation in the hypothalamus [46]. Interestingly, in sst2 knock-out (KO) mice, the glutamatergic responses were increased in the hippocampal slices [47], suggesting that SST exerts an inhibitory tone on glutamatergic transmission through sst2 activation [48]. However, the activation of sst4, selectively expressed in the hippocampal CA1, increased the hippocampal glutamatergic responses, an effect inhibited by the activation of sst2, suggesting the possible functional interaction of these subtypes [49].…”
Section: Somatostatin Receptorsmentioning
confidence: 99%